Studi Penurunan Tekanan Akibat Aliran Melalui Katup - Arfan, Arfan; Salimin, Salimin; Imran, Al Ichlas (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
The purpose of this study was to determine the effect of flow rate (Q) on pressure drop (ΔP) and to find out how much pressure drop value (ΔP) and loss coefficient (k) occurred in valves. The method used is an experimental study, using a series of test  installations.  In  this  study  the  free  variables  used  were  the  flow  rate  that passes through the valve pipe, for bound variables are reynolds number (Re), loss coefficient (K) and pressure decrease (ΔP). Based on the results of the study, it can be concluded that the greater the discharge of outflow (Q) the smaller the value of pressure reduction (ΔP) that occurs, and vice versa. The pressure drop value (ΔP) obtained at the valve opening was 16.6% for each point of ΔP1-2, ΔP1-3, ΔP1-4, ΔP1-5 of 18846.1 Pa; 19129.2 Pa; 20506.1 Pa; 20897.0 Pa. While the amount of friction coefficient value (hf) obtained at the valve opening is 99.6% for each point hf2, hf3, hf4, hf5 which is 0.188 mH2O; 0.263 mH2O; 0.338 mH2O; 0.414 mH2O. Keywords: Valve, Discharge, Head Loss, Pressure Drop